Robbing Host Phosphatidic Acid to Survive: A Strategy of a Fly Parasite. Issue 5 (May 2019) - Coppens, Isabelle
Abstract : Drosophila flies can be infected by an obligate fungal intracellular parasite, Tubulinosema ratisbonensis, resulting in a swollen abdomen and often death. Within the fly, the parasite multiplies in the cytoplasm of adipocytes of the fat body, feeds on host lipid droplets, and has a specific requirement for dietary phosphatidic acid.